2023
DOI: 10.1002/alz.13413
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the A/T/N profiles in PET, CSF, and plasma biomarkers with Alzheimer's disease neuropathology at autopsy

Abstract: INTRODUCTIONTo examine the extent to which positron emission tomography (PET)‐, cerebrospinal fluid (CSF)‐, and plasma‐related amyloid‐β/tau/neurodegeneration (A/T/N) biomarkers are associated with Alzheimer's disease (AD) neuropathology at autopsy.METHODSA total of 100 participants who respectively underwent antemortem biomarker measurements and postmortem neuropathology were included in the Alzheimer's Disease Neuroimaging Initiative (ADNI). We examined the associations of PET‐, CSF‐, and plasma‐related A/T/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Currently, plasma assays have not received regulatory approval, but a few assays based on standalone amyloid or tau biomarkers have received the FDA breakthrough device designation (Table 1). However, recent studies have shown substantial variation in accuracy of plasma-related A/T/N biomarker assays with respect to PET visual reads or CSF reference standard (60-90%) [22][23][24][25].…”
Section: Taumentioning
confidence: 99%
“…Currently, plasma assays have not received regulatory approval, but a few assays based on standalone amyloid or tau biomarkers have received the FDA breakthrough device designation (Table 1). However, recent studies have shown substantial variation in accuracy of plasma-related A/T/N biomarker assays with respect to PET visual reads or CSF reference standard (60-90%) [22][23][24][25].…”
Section: Taumentioning
confidence: 99%
“…Compared to necropsy as the gold standard, PET and CSFrelated biomarkers in combination showed high concordance with the pathological stage; alone, they showed high accuracy in discriminating autopsy-confirmed AD. However, the plasma-related biomarkers alone showed better discriminative performance only when combined with the apolipoprotein E (APO) Eε4 genotype [40]. In this context, biomarkers that accurately reflect disease progression and have prognostic capabilities are also needed.…”
Section: Markers In Biological Fluids (Cerebrospinal Fluid and Plasma)mentioning
confidence: 99%